Sport and art - towards comprehensive education of a beautiful human - Pędraszewska, Barbara (Physical education, sport and olympism from a pedagogical perspective, 2023)
One of the elements of comprehensive education is aesthetic education, treated as the totality of conscious influences on human and their actions in order to sensitise them to beauty, goodness and truth, as well as to achieve the development of creative activity, expression, and skilful reception of art through contact with its various fields. Sport provides a lot of emotions and creative inspiration for artists who can experience double emotions - those related to the beauty of the body and the athlete's effort, sports competition, as well as artistic expression in various fields of art, i.e.: literature, painting, sculpture, music, film or contemporary audiovisual forms.In the article, the authors attempt to indicate examples of such inspiration with sport in selected artists in various fields of art, thus pointing out the significant relationship between sport and art in the comprehensive development of a beautiful, sensitive to others human beings.